Post-eclosion decline in 'knock-down' thermal resistance and reduced effect of heat hardening in Drosophila melanogaster. - Pappas, C.; Hyde, D.; Bowler, K.; Loeschcke, V.; Sorensen, J.G. (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2007)
The dependency of knock-down resistance on age, from 0 to 12 days post eclosion, was studied in two lines of Drosophila melanogaster, one selected for knock-down resistance and one unselected control. Additionally, the inducible Hsp70 expression level was assessed at maintenance temperature and after a heat hardening treatment (1 h at 35 degrees C) at the same ages. Knock-down resistance decreased roughly linearly with age in both control and knock-down selected lines and in both sexes regardless of maintenance temperature. Hsp70 expression, however, fell only from day 0 to day 3 and was thereafter changed little. Acclimation did not result in detectable difference between lines. The effect of hardening was only significant for control flies. This suggests that the increased knock-down resistance of the selected line was reached at the expense of hardening ability.